Investigation of sulfoxaflor, flupyradifurone and their transformation products in plant-based food matrices. (February 2022) - Dal Bello, F.; Medana, C.; Guarino, B.; Dioni, A.; Fabbri, D.; Calza, P.
Abstract: Sulfoxaflor and flupyradifurone, two pesticides belonging to sulfoximins and butenolides, are widely used to treat crops and fruits. In order to amplify the detection of pollutants, we aimed to identify also molecules deriving from the parent pesticides. We studied their photoinduced transformation and identified their main transformation products by applying a laboratory simulation and by employing HPLC-HRMS to characterize them. We detected three transformation products from sulfoxaflor, whose formation involved the conversion of cyanamide group into a ureic group and the detachment of the side chain. Flupyradifurone transformation proceeded through the formation of seven transformation products and three of them were recognized in this study for the first time; it involved hydroxylation and breakage of the molecule with the detachment of the pyridine or furan ring. These results will allow enlarging the extent of TPs to be screened in food matrices. Pesticides and their transformation products were then determined in 67 samples of fruits, leaves, honey and pollen by applying QuECHERs for sample pre-treatment and HPLC-MS/MS for their quantification. The presence of flupyradifurone was detected in different samples of honey at concentration level of 10–15 μg/kg. Highlights: Sulfoxaflor and flupyradifurone were investigated. We identified their transformation products via a laboratory simulation and HPLC-HRMS. We detected 3 transformation products from sulfoxaflor and 7 from Flupyradifurone. They were searched in 67 samples of fruits, leaves, honey and pollen. The presence of flupyradifurone was detected in different samples of honey.